TRIM21 aggravates cardiac injury after myocardial infarction by promoting M1 macrophage polarization - Zhiqiang Li; Xiangdong Liu; Xingxu Zhang; Wenming Zhang; Mengmeng Gong; Xiaoming Qin; Jiachen Luo; Yuan Fang; Baoxin Liu; Yidong Wei (Frontiers in Immunology, 2022)
Macrophage polarization followed by myocardial infarction (MI) is essential for wound healing. Tripartite motif-containing protein 21 (TRIM21), a member of E3 ubiquitin ligases, is emerging as a mediator in cardiac injury and heart failure. However, its function in modulating post-MI macrophage polarization remains elusive. Here, we detected that the levels of TRIM21 significantly increased in macrophages of wild-type (WT) mice after MI. In contrast, MI was ameliorated in TRIM21 knockout (TRIM21-/-) mice with improved cardiac remodeling, characterized by a marked decrease in mortality, decreased infarct size, and improved cardiac function compared with WT-MI mice. Notably, TRIM21 deficiency impeded the post-MI apoptosis and DNA damage in the hearts of mice. Consistently, the accumulation of M1 phenotype macrophages in the infarcted tissues was significantly reduced with TRIM21 deletion. Mechanistically, the deletion of TRIM21 orchestrated the process of M1 macrophage polarization at least partly via a PI3K/Akt signaling pathway. Overall, we identify TRIM21 drives the inflammatory response and cardiac remodeling by stimulating M1 macrophage polarization through a PI3K/Akt signaling pathway post-MI.